Energy Consumption and Emissions of Diesel-CNG Dual Fuel Engine at High Load Operation - Ismail, Muammar Mukhsin; Fawzi, Mas; Theerayut, Leevijit; Zulkifli, Fathul Hakim; Osman, Shahrul Azmir; Taweekun, Juntakan (International Journal of Integrated Engineering, 2020)
Global warming and energy sustainability issues are among the major world concern. In Malaysia, National Automotive Policy (NAP) has been implemented and revised to enhance the usage of the green energy, in order to achieve a low carbon emission and energy efficient vehicle. Researchers keep striving to find alternative solutions to power vehicles by cleaner energy efficiently. Compressed Natural Gas (CNG) has lower carbon emission and higher energy density compared to common petroleum fuel. It provides an opportunity to power the vehicle cleanly. Thus, it has been used as an alternative for fueling gasoline engine. However, CNG fuel is difficult to be applied on diesel engine. Unlike gasoline engine, diesel engine does not have spark plug and its fuel is combusted through compression in cylinder. Since CNG has high octane number, it is difficult to self-ignite in diesel engine. Therefore, Diesel-CNG Dual Fuel (DDF) system is applied. The system use CNG as part fuel and certain amount of diesel pilot fuel is injected into the cylinder to ignite the combustion. DDF engine may potentially reduces Carbon Dioxide (CO2) emission. However, high fuel consumption and Nitrogen Oxide (NOX) emission have been observed at high load engine operation due to improper fuel ratio. In this study, four ratios of DDF were tested and compared with 100% diesel: 90D10G, 80D20G, 70D30G, 60D40G. It was found that each of the fuel ratio behaved differently in terms of brake specific energy consumption (BSEC) and exhaust emissions.